How Will Social Media Shape Public Health Narratives in the Next Decade? A Qualitative Scenario-Based Study - Wong, Yoko; Seng Neo, Xian (Journal of Foresight and Health Governance, 2024)
This study explores how social media will shape public health narratives over the next decade. A qualitative scenario-based approach was employed, utilizing semi-structured interviews with 30 experts in public health communication, digital media strategy, and health policy. Participants were recruited through online announcements and professional platforms, ensuring diverse expertise. Data collection continued until theoretical saturation was reached, and the interviews were transcribed and analyzed using NVivo software. Thematic analysis was conducted to identify key themes related to social media's evolving role in public health narratives, with a focus on misinformation management, AI-driven content curation, crisis communication, and regulatory challenges. The analysis revealed that social media plays an increasingly central role in public health communication by enabling rapid crisis responses, facilitating digital health campaigns, and fostering community engagement. However, experts highlighted concerns about misinformation, algorithmic biases, and ethical AI use in digital health messaging. The study also found that interactive public health education, social listening, and citizen science are emerging trends that will shape future public health narratives. Additionally, disparities in digital access and corporate influences on health communication were identified as ongoing challenges that require strategic interventions. Participants emphasized the need for regulatory frameworks, stronger fact-checking mechanisms, and inclusive digital literacy initiatives to improve public health messaging on social media. The findings suggest that while social media offers significant opportunities for advancing public health communication, it also presents risks that must be managed through improved governance, ethical AI implementation, and public engagement strategies. Future public health efforts must focus on misinformation control, AI transparency, and digital equity to ensure that social media contributes positively to global health outcomes.